2007
DOI: 10.1097/00042871-200701010-00728
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Face of Phase I Cancer Clinical Trials: New Challenges in Study Requirements.

Abstract: Background-Phase I studies in cancer have changed in recent years. With the advent of new less toxic targeted agents, more patients may now be candidates for new drug studies earlier in the course of their disease. It is to the advantage of the members of the oncology community to know more about the details and requirements for participation in early phase clinical trials so they can advocate for their patients and help them decide when such trials may be an appropriate choice. In order to examine the work in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Perhaps in part as a result of the increasing desire to reduce toxicities, as well as the historic low benefit rate of many drug interventions in oncology, adverse events are closely scrutinized and patients enrolled in clinical trials are intensively monitored. The earliest stage trials, that is, phase I trials, commonly require frequent repetition of a variety of tests or procedures, such as vital sign measurements, physical examinations, ECG monitoring (in order to evaluate QT interval and rhythms), blood draws for PK analyses and for pharmacodynamic impact, non-PK blood draws, eye exams, endocrine follow-up, and other specialized examinations for safety assessment and/or for data collection [1][2][3][4]. In phase II and III studies, Roche et.…”
Section: What Are the Monitoring Requirements For Early-phase Trials?mentioning
confidence: 99%
See 2 more Smart Citations
“…Perhaps in part as a result of the increasing desire to reduce toxicities, as well as the historic low benefit rate of many drug interventions in oncology, adverse events are closely scrutinized and patients enrolled in clinical trials are intensively monitored. The earliest stage trials, that is, phase I trials, commonly require frequent repetition of a variety of tests or procedures, such as vital sign measurements, physical examinations, ECG monitoring (in order to evaluate QT interval and rhythms), blood draws for PK analyses and for pharmacodynamic impact, non-PK blood draws, eye exams, endocrine follow-up, and other specialized examinations for safety assessment and/or for data collection [1][2][3][4]. In phase II and III studies, Roche et.…”
Section: What Are the Monitoring Requirements For Early-phase Trials?mentioning
confidence: 99%
“…Several authors [1,2] have discussed issues that emerge as a result of the monitoring directive, including an exponential growth in tests, the rigidity of the rules governing the proper follow-up of patients, and duplication of tests on multiple occasions. In a paper published in 2002 [2], it was estimated that one full-time equivalent research staff was required for enrollment of every 10 patients in a moderate-intensity phase III study.…”
Section: What Are the Monitoring Requirements For Early-phase Trials?mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well documented that the complexity of clinical trials has increased substantially in this period of time (9)(10)(11)(12)(13)(14)(15). Hence, the purpose of this review was to describe the frequency with which compliance problems are observed, with the rationale for the study being that compliance in the face of increasing protocol complexity might present challenges that should be ascertained, so that they can be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Jamerson 5 also makes the case for hospital departmental review and involvement, assessment of the ability to integrate study activities into the hospital structure, assessment of the resources needed to support the research, determination of whether the hospital will contribute financially to the research, and explicit decision making regarding the assumption of institutional risk. Despite the recognition that US patients increasingly live with multiple chronic conditions 6 and that clinical trial protocols have become more procedure and resource intensive and costly, [7][8][9] there has not been a corollary recognition of the increasing need for hospitals to understand and manage research activities occurring within their facilities. Our organization is a hospital system with 9 acute care hospitals, including an academic teaching hospital (affiliated with a university medical school) with a Level 1 Trauma Center, 1 specialty rehabilitation hospital, numerous specialized clinics, and a LifeFlight Program with a 6-helicopter fleet (Geisinger, Danville, PA).…”
Section: Introductionmentioning
confidence: 99%